Hodnocení finanční situace podniku - Štáfová, Markéta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Tato diplomová práce hodnotí finanční situaci společnosti Královopolská RIA, a.s. v období let 2002 až 2006 a to prostřednictvím vybraných metod finanční analýzy. Obsahuje návrhy možných řešení zjištěných problémů, které mají vést ke zlepšení celkové finanční situace podniku v nadcházejících letech.

This thesis analyses the financial situation of the company Královopolská RIA, a.s. in the years 2002 to 2006 at the basis of sesected methods of the financial analysis. It comprieses proposals of possible solutions of indentified problems which should result in the improvement of financial situation of the company in future years.
The Evaluation of the Financial Situation’s Company
Keywords: finanční zdraví; finanční analýza; elementární metody finanční analýzy; finanční ukazatelé; horizontální a vertikální analýza; poměroví ukazatelé; likvidita; zadluženost; aktivita; rentabilita; Financial health; financial analysis; basis methods of financial analysis; financial indices; horizontal and vertical analysis; ratio indices; solidity; insolvency; activity; profitability